Nonocclusive Mesenteric Ischemia and Interventional Local Vasodilatory Therapy: A Meta-Analysis and Systematic Review of the Literature. (February 2020) - Stahl, Klaus; Rittgerodt, Nina; Busch, Markus; Maschke, Sabine K.; Schneider, Andrea; Manns, Michael P.; Fuge, Jan; Meyer, Bernhard C.; Hoeper, Marius M.; Hinrichs, Jan B.; David, Sascha
Background: Intensive care patients with nonocclusive mesenteric ischemia (NOMI) show mortality rates of 70% to 90%. Besides emergency surgery, different interventional local vasodilatory treatment (LVT) attempts have been described. We performed a systematic review and a meta-analysis to evaluate feasibility, efficacy, and tolerability of LVT in patients with life-threatening NOMI. Methods: Searches of PubMed, EMBASE, Web of Science, and Cochrane Library databases were performed until February 2019. Measured outcomes included immediate technical success rates (as indicated by mesenteric vasodilation on angiography or clinical improvement) and adverse events (AEs). Therapeutic efficacy was measured by the assessment of overall mortality. Results: Twelve studies (335 patients, 245 received LVT) from 1977 to 2018 were included. All studies were retrospective (4 comparative and 8 noncomparative). Different intra-arterial vasodilators (4× papaverine, 6× prostaglandin E1, 1× tolazoline/heparin, 1× tolazoline + iloprost) were reported. Initial technical success rate was 75.9% (95% confidence interval [CI], 55.1%-89%, P = .017) with an AE rate of 2.9% (95% CI: 1.3%-6.6%; P = .983). Overall mortality in LVT patients was 40.3% (95% CI: 28.7%-53%, P = .134). In 4 studies, outcomes were compared between patients receiving LVT to those who received standard of care (odds ratio for death in LVT patients was 0.261 [95% CI: 0.095-0.712, P = .009]). Conclusions: Local vasodilatory treatment appears to be safe in patients with NOMI and might have the potential to at least partially reverse mesenteric vasoconstriction features in control angiographies. However, with no randomized and prospective studies available yet, the overall quality of published studies has to be considered as low; therefore, it is not possible to draw generalizable conclusions from the present data concerning clinical end points. Its application might hold promise as a rescue treatment strategy and deserves further evaluation in randomized controlled trials.